Od alienacji do akceptacji. Antysemityzm - antyjudaizm - antyżydowskość - antysyjonizm - Szczerbiński, Waldemar (Studia Europaea Gnesnensia, 2012)
This presentation concerns the problem of the social withdrawal of the Jews in other communities both now and in the past. The life in the diaspora brought about a certain amount of tension conditioned by economic, political, social, moral, national or religious factors. There emerged various attitudes of non-Jews towards the Jews customarily called anti-Semitism, anti-Judaism, anti-Jewishness as well as anti-Zionism. All the aforementioned phenomena have common grounds: such was the price of constructing, protecting, preserving and developing one’s identity in a strange community. There are, however, essential differences between these phenomena and this is usually forgotten. Consequently, any attempt at subsuming all of them under the term ‘anti-Semitism’ is unfounded and unjustifiable. The presentation aims first and foremost at characterising the above phenomena and particularly the differences and similarities between them as this affects their proper understanding and evaluation.